Tataniaga Dan Implementasi Dumping Pada Bisnis Ayam Pedaging Di Pulau Sumba - Karolina A. Rewa; Wahyu Wijayanto (Universitas Kristen Wira Wacana Sumba, 2014)
The purpose of this study is to know the trading system and the implementation of broiler chicken business on the island of Sumba. The primary data is technically collected through in-depth interviews. And the data is analyzed with descriptive qualitative technique.The result shows that: the trading system of broiler chicken business in the Sumba island using two chain-links marketing, that is, direct marketing and indirect marketing chain.The implementation of dumping system on the chicken broiler business in Sumba Island caused by several things: lots of competitors, the same time of harvest schedule at the level of chicken breeders, the desire of breeders to monopolize and control the market and consumers, and breeders have a large number of chickens so that they (the breeders) decide to put on sale their chicken broiler price temporary and when the breeders have monopolized the market then the dumping practices discontinued.The problems in chicken broiler breeding business; 1) difficulty in obtaining the means of production (fodder, seeds and medicines); 2) obstacles in marketing of broiler chickens; 3) difficulty in getting the help of financial micro-credits; and 4)difficulty whe nthe chicken broiler affected by disease outbreaksKeywords: Trading System, Dumping, and Chicken Broiler Breeders